Religiosity and Islamic Banking Product Decision: Survey on Employees of PT Telekomunikasi Indonesia - Abdul Mukti Soma; Ina Primiana; Sudarso K Wiryono; Erie Febrian (ETIKONOMI, 2017)
The objective of this research is to examine the religiosity on Islamic banking product decision. A survey method was employed using a sample of 2.627 employees at different level of education, level of income, gender, age, marital status, length of service, work location (provincial based), ownership of conventional banking products as well as ownership of sharia banking products among employees of PT. Telekomunikasi Indonesia. The study also developed valid and reliable scales for religiosity and selection of sharia banking product.  The ﬁndings of the study revealed that dimensions of religiosity affected understanding of Islamic Banking Concept and also affected Bank Selection Criteria. Future research is required to investigate private employees and semi government employees, even in military institutions to find different figure of religiosity and preference of sharia banking products, by identifying the speciﬁc areas of religiosity that have particular impact in determining the sharia banking products.DOI: 10.15408/etk.v16i1.4379